The Influence of Motivation on Learning Outcomes in Physical Education, Sports, and Health of Junior High School Students in Air Kumbang District - Alamsyah, Yakub; Waspodo, Waspodo; Ibagus Endrawan (Yayasan Insan Mulia Bima, 2024)
This study aims to determine the motivation Grade VIII junior high school 1 and junior high school 2 in District Water Beetles in participating in PE lessons. This research is quantitative descriptive with survey method and data retrieval technique using a questionnaire which was divided into a couple of factors. The results showed that:1) The test results of the validity of the talent factor declared invalid because the value rhitung minimum 0.401> rtabel amounted to 0,316, physical factors 0.671> rtabel namely 0,308, factors skills 0.751> rtabel ie 0,308, the factor of discipline lowest value 0.435> rtabel amounted to 0,316, knowledge factor 0.347 > rtabel amounted to 0,316, of the factors hobby 0.449> rtabel amounted to 0,316, a factor parents lowest value 0.661> rtabel is 0,308, of the factors friend 0.441> rtabel amounted to 0,316, the factors teacher 0,397> rtabel amounted to 0,316, at school factors lowest value 0,470> rtabel amounted to 0,316, while the infrastructure factor the lowest value is 0.318> rtabel amounted to 0,316. So, we can conclude from the results of a calculation on all the factors involved in otherwise valid because rhitung in greater than rtabel. 2) From the Test Reliability Realibity results showed the value of Cronbach Alpha coefficient of 0.284.